Designing Automatic Sprinklers and Web-Based Plant Monitoring Using a Microcontroller - Ferri Ojak Immanuel Pardede; Benjamin Albert Simamora (Jurnal Mantik, 2020)
Utilization of industrial development 4.0 and IoT in the agricultural sector is still very minimal even though with the use of IoT technology and industrial development 4.0. in the agricultural sector can increase agricultural productivity. Efficiency in terms of watering plants manually is still lacking. The solution to this problem is to take advantage of technological developments, namely presenting a new innovation in watering plants by designing plant watering tools and monitoring using a web-based arduino Mega 2560 Rev3 microcontroller. The sensors to be used are: YL-69, DHT11 and HY-SRF-05 as the water tank volume sensor from the device, and using the ESP-01 as a WiFi module. If one of the earthen boxes is dry, the tool will water the dry soil box. This tool will also display the sensor data to the LCD screen, then send the sensor data to the database and the monitoring results will be presented in web form. The tool that has been designed can be used as a tool for watering plants for farmers and the general public as well as for up-to-date monitoring of plants.